Seasonal Changes Of Some Blood Component Of Barbus sharpyie In Al-emaria Marsh water - Salman Abudlhasan, Ahmed (University of Thi-Qar Journal, 2022)
The ratio of blood component and some special variable of Barbus sharpyie specimen has been measured during the hot months of summer, and the cold months of winter extreme changes in ratio of Hb , P.C.V. , RBC , WBC and the effort of blood component have been noticed, which proves environmental and physiological fatigue undergone by this species of Iraqi fish . Also, showed a clear effects between rising in temperatures and the amounts of hemoglobin, P.C.V. , RBC , WBC .